Successful use of atenolol in the treatment of a severe infantile hemangioma. - Harnett, D.; Templeton, C. (European Journal of Pediatric Dermatology, 2012)
Off-label use of propranolol to treat severe infantile hemangiomas has become common since an incidental finding demonstrated the potential efficacy of this therapy in 2008. Numerous published reports confirming the efficacy of this therapy have followed, but relatively few that explore the use of other β-blockers. We present a case of the successful use of atenolol to treat an infantile hemangioma in an 11-week-old girl. Initial therapy with propranolol induced significant regression of the hemangioma. However, treatment was complicated by the fact that the child often refused to swallow the three times daily dosing resulting in rebound regrowth of the hemangioma. Propranolol was discontinued in favor of an experimental once daily regimen of atenolol, which induced tumor involution over a period of approximately two weeks without side effects.